2007
DOI: 10.1016/j.ydbio.2006.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Impaired mesenchymal cell function in Gata4 mutant mice leads to diaphragmatic hernias and primary lung defects

Abstract: Congenital diaphragmatic hernia (CDH) is an often fatal birth defect that is commonly associated with pulmonary hypoplasia and cardiac malformations. Some investigators hypothesize that this constellation of defects results from genetic or environmental triggers that disrupt mesenchymal cell function in not only the primordial diaphragm but also the thoracic organs. The alternative hypothesis is that the displacement of the abdominal viscera in the chest secondarily perturbs the development of the heart and lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
170
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(184 citation statements)
references
References 92 publications
10
170
4
Order By: Relevance
“…Although the cause of death was not identified in these studies, a higher incidence of cardiovascular defects (27,53) was identified in Gata4 ϩ/Ϫ animals compared with wild-type littermates. To determine whether Gata4…”
Section: Gata4mentioning
confidence: 81%
See 3 more Smart Citations
“…Although the cause of death was not identified in these studies, a higher incidence of cardiovascular defects (27,53) was identified in Gata4 ϩ/Ϫ animals compared with wild-type littermates. To determine whether Gata4…”
Section: Gata4mentioning
confidence: 81%
“…ϩ/Ϫ heterozygotes have been reported to exhibit partial postnatal lethality when backcrossed onto a C57/BL6 background (27,53). Although the cause of death was not identified in these studies, a higher incidence of cardiovascular defects (27,53) was identified in Gata4 ϩ/Ϫ animals compared with wild-type littermates.…”
Section: Gata4mentioning
confidence: 89%
See 2 more Smart Citations
“…FOG2 was shown to be an important regulator of Gata-4 in the developing heart, and both genes are co-expressed during cardiac embryogenesis. 28 Interestingly, C57Bl/6 mice that were heterozygous for a deletion mutation of the Gata-4 gene have midline diaphragmatic defects, 29 suggesting that abnormal regulation of Gata-4 by FOG2 might also be important for diaphragm development. FOG2 also binds to the ligandbinding domain of chicken ovalbumin upstream promoter transcription factor II (COUP-TFII; also known as NR2F2).…”
Section: Discussionmentioning
confidence: 99%